IRAN IN THE MINDS OF THE ISRAELIS - Levy, Mordechai (Przegląd Strategiczny, 2015)
The foreign policy of Israel towards Iran relies on the shared understanding of the leadership and the public in Israel of the reality, and hence agreement is also built regarding the steps that should be undertaken regarding Iran and its nuclear program. Through research of the social representations, it will be possible to identify the core images and bases of agreement of society in Israel and to identify the existence of alternative understanding of subgroups, which exist in parallel in the society. The findings indicate that the heterogeneity in Israeli society is expressed also in the collection of images and explanations regarding the nature of the State of Israel and regarding the Iranian threat. In the Jewish group it is possible to identify two systems of core representations: the first is collection of images of the Holocaust and the second is images of the Israeli-Arab conflict. In the Arab group differences among its sub-groups was found. Groups whose sons serve in the Israeli military created discourse similar to the Jewish group, and the other Arabs formed images around the status as a minority in the Jewish nation state.